Self-control Depletion and the General Theory of Crime - Muraven, Mark (Journal of quantitative criminology, 2006)
Criminological research on self-control focuses mainly on self-control failure. Such research has not, however, investigated the consequences of exercising self-control for the individual doing so. The present study investigates this issue within the framework of both criminological self-control theory and research on self-control depletion from social psychology, which depicts self-control as akin to a “muscle” that is “depletable” by prior use [Muraven and Baumeister (2000) Psycholog Bull 126:247–259]. Results are presented from a laboratory experiment in which students have the opportunity to cheat. Both “trait self-control,” as measured by the Grasmick et al. [(1993) J Res Crime Delinq 30:5–29] self-control inventory, and “self-control depletion” independently predicted cheating. The implications of these findings are explored for criminological perspectives on self-control and offender decision-making.